\(\frac{5\sqrt{2}}{\sqrt{5}+\sqrt{3}}\) giải giúp nhé
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Đặt \(\hept{\begin{cases}\sqrt{5-x}=a\\\sqrt{x-3}=b\end{cases}}\)
=> a2 + b2 = 2
PT \(\Leftrightarrow\frac{a^3+b^3}{a+b}=2\Leftrightarrow\frac{\left(a+b\right)\left(a^2-ab+b^2\right)}{a+b}=2\)
\(\Leftrightarrow2-ab=2\Leftrightarrow ab=0\)
\(\Leftrightarrow\orbr{\begin{cases}\sqrt{5-x}=0\\\sqrt{x-3}=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=5\\x=3\end{cases}}\)
`(sqrtx+2)/(sqrtx-3)-(sqrtx+1)/(sqrtx-2)-(3(sqrtx-1))/(x-5sqrtx+6)`
đk:`x>=0,x ne 4,x ne 9`
`=((sqrtx+2)^2-(sqrtx+1)(sqrtx+3)-3(sqrtx-1))/(x-5sqrtx+6)`
`=(x+4sqrtx+4-x-4sqrtx-3-3sqrtx+3)/(x-5sqrtx+6)`
`=(4-3sqrtx)/(x-5sqrtx+6)`
22,
1, Đặt √(3-√5) = A
=> √2A=√(6-2√5)
=> √2A=√(5-2√5+1)
=> √2A=|√5 -1|
=> A=\(\dfrac{\sqrt{5}-1}{\text{√2}}\)
=> A= \(\dfrac{\sqrt{10}-\sqrt{2}}{2}\)
2, Đặt √(7+3√5) = B
=> √2B=√(14+6√5)
=> √2B=√(9+2√45+5)
=> √2B=|3+√5|
=> B= \(\dfrac{3+\sqrt{5}}{\sqrt{2}}\)
=> B= \(\dfrac{3\sqrt{2}+\sqrt{10}}{2}\)
3,
Đặt √(9+√17) - √(9-√17) -\(\sqrt{2}\)=C
=> √2C=√(18+2√17) - √(18-2√17) -\(2\)
=> √2C=√(17+2√17+1) - √(17-2√17+1) -\(2\)
=> √2C=√17+1- √17+1 -\(2\)
=> √2C=0
=> C=0
26,
|3-2x|=2\(\sqrt{5}\)
TH1: 3-2x ≥ 0 ⇔ x≤\(\dfrac{-3}{2}\)
3-2x=2\(\sqrt{5}\)
-2x=2\(\sqrt{5}\) -3
x=\(\dfrac{3-2\sqrt{5}}{2}\) (KTMĐK)
TH2: 3-2x < 0 ⇔ x>\(\dfrac{-3}{2}\)
3-2x=-2\(\sqrt{5}\)
-2x=-2√5 -3
x=\(\dfrac{3+2\sqrt{5}}{2}\) (TMĐK)
Vậy x=\(\dfrac{3+2\sqrt{5}}{2}\)
2, \(\sqrt{x^2}\)=12 ⇔ |x|=12 ⇔ x=12, -12
3, \(\sqrt{x^2-2x+1}\)=7
⇔ |x-1|=7
TH1: x-1≥0 ⇔ x≥1
x-1=7 ⇔ x=8 (TMĐK)
TH2: x-1<0 ⇔ x<1
x-1=-7 ⇔ x=-6 (TMĐK)
Vậy x=8, -6
4, \(\sqrt{\left(x-1\right)^2}\)=x+3
⇔ |x-1|=x+3
TH1: x-1≥0 ⇔ x≥1
x-1=x+3 ⇔ 0x=4 (KTM)
TH2: x-1<0 ⇔ x<1
x-1=-x-3 ⇔ 2x=-2 ⇔x=-1 (TMĐK)
Vậy x=-1
\(\sqrt{\frac{3+\sqrt{5}}{3-\sqrt{5}}}+\sqrt{\frac{3-\sqrt{5}}{3+\sqrt{5}}}\)
\(=\frac{3+\sqrt{5}}{2}+\frac{3-\sqrt{5}}{2}=3\)
PS: Nhân lượng liên hiệp
ĐÁP ÁN :2,725811
Ta có:\(\frac{5\sqrt{2}}{\sqrt{5}+\sqrt{3}}=\frac{5\sqrt{2}\left(\sqrt{5}-\sqrt{3}\right)}{5-3}=\frac{5}{2}\left(\sqrt{10}-\sqrt{6}\right)\)